2020
DOI: 10.1002/csc2.20102
|View full text |Cite
|
Sign up to set email alerts
|

Identification of waxy cassava genotypes using fourier‐transform near‐infrared spectroscopy

Abstract: High-throughput phenotyping tools that allow the early and accurate evaluation of important agronomic traits have gained space in current breeding programs. The aim of this study was to evaluate the potential of Fourier-transform near-infrared spectroscopy (FT-NIRS) to identify cassava (Manihot esculenta Crantz) clones with waxy starch (i.e., amylose-free) by screening leaves rather than roots, and to validate prediction models for classifying these phenotypes. We analyzed the spectra of 162 waxy and 180 nonwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…In the present study, seeds from segregating populations of cassava for waxy starch were used as sample material for the identification/classification of waxy and non-waxy genotypes by near-infrared spectroscopy (NIRS). A previous study using spectral data collected from leaf tissue allowed the early and accurate identification of waxy genotypes ( Carmo et al., 2019 ). The NIRS technique allows capturing differences in the chemical constitution of plants because of the expression of different genes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, seeds from segregating populations of cassava for waxy starch were used as sample material for the identification/classification of waxy and non-waxy genotypes by near-infrared spectroscopy (NIRS). A previous study using spectral data collected from leaf tissue allowed the early and accurate identification of waxy genotypes ( Carmo et al., 2019 ). The NIRS technique allows capturing differences in the chemical constitution of plants because of the expression of different genes.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, NIRS can serve as an important predictor of these compounds in organic substances. Carmo et al (2019) evaluated Fourier-transform near-infrared spectroscopy (FT-NIRS) for indirect, early identification of waxy starch cassava genotypes by screening samples of dried, macerated leaves. In this study, the distribution between the classes of waxy and non-waxy genotypes was similar, and the results showed high accuracy, deeming it a potential technique for the classification of waxy genotypes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Machine learning models are an efficient tool and have been widely used in different agriculture approaches to unravel, quantify, and understand data-intensive processes [ 47 ]. However, the predictive ability depends on the dataset under analysis; for this reason, it is interesting to evaluate different approaches in order to explore differences in algorithms that may benefit the predictions [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…They achieved a confidence interval of 95% for the two models. Carmo et al reported the phenotyping of waxy starch cassava using Fourier Transform Infrared (FTIR) analysis on the leaves rather than the root [121]. This method has the potential to make analysis much easier for breeders, as the leaves are formed before the root.…”
Section: Cassava and Wheatmentioning
confidence: 99%